Implementasi Program Kredit Usaha Pembibitan Sapi (KUPS) di Kabupaten Sragen - Dwiningtyas Padmaningrum (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2012)
The study examined the implementation and constraints of Cattle Breeding Loan Program (KUPS) in Sragen. The study used a descriptive qualitative approach, where data on program implementation and constraints were collected through interviews with informants and documents. Informants were stipulated purposively, which represent the entire stakeholders, i.e. from element of farmer group/combined groups of cattle breeder, element banking institutes as well as the government element. The KUPS program for groups/combined groups of breeder could not yet be fully implemented due to several technical and economical constraints. Technical constraints included lack of technical skills and management, there was no breeding companies/cooperatives as partner, difficulty in finding good quality of cattle and lack of assistance. Economic constraints included fluctuations in market prices, payment of the credit, short credit period, and risk of failure of artificial insemination and animal deaths. To increase participation and successfulness this program, it is needed the realization of a partnership with breeding companies, technical and management assistances which involve the stakeholders, banks and partners in the mentoring and monitoring.